COMPARATIVE EVALUATION OF EFFICACY OF CYANOACRYLATE AND SUTURE MATERIAL IN THE MANAGEMENT OF OPERATIVE SKIN WOUNDS - TRIPATHI, SOMESH; DIXIT, PRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Closing wounds are a fundamental aspect of surgery. Both patients and surgeons hope that no scars remain once a wound has healed. This study examined the effectiveness of cyanoacrylate and suture material in closing operational skin wounds in terms of time required for closure of the operative incision and problems associated with it. Methods: Forty-two individuals who had emergency surgery participated in this comparative analysis. The study evaluated how the identical patient’s abdominal incisions were closed on the skin. Relevant surgical information, such as signs of inflammation, discomfort, possible discharge, wound dehiscence, and sinus, was recorded both during and after the operation. Results: In the adhesive application group, it took 1.5 min (95 s), but it took 4.1 min (248 s) in suturing group for the closure of a <5-cm incision. Of the 32 patients in the adhesive group, 4 (12.5%) showed erythema and warmth, 3 (9.3%) showed discomfort, and 6 (18.7%) showed discharge. All other problems, excluding dehiscence, were less severe in the sticky group. Conclusion: For patients undergoing emergency laparotomies, cyanoacrylate appears to be a safe and cost-effective alternative to sutures. For a conclusive outcome, a high number of case groups are needed, but the observed results were only on a small number of case groups.